2017
DOI: 10.1177/1468087417731698
|View full text |Cite
|
Sign up to set email alerts
|

A control-oriented combustion model for a turbulent jet ignition engine using liquid fuel

Abstract: A control-oriented engine model is necessary for developing and validating the associated engine control strategies. For engines equipped with the turbulent jet ignition system, the interaction between the pre-and main-combustion chambers should be considered in the control-oriented model for model-based control strategies that optimize the overall thermal efficiency in real-time. Therefore, a two-zone combustion model based on the newly proposed parametervarying Wiebe function is proposed. Since the engine us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The burn dependency between pre- and main-combustion chambers was adapted from the already developed and tested concept of a parameter-varying Wiebe function 3,17 with a number of readjustments. Song et al 3,17 reported a high correlation between the mass flow rate of the turbulent jets and the rate of combustion in the main chamber. Thus, they linked the intensity of the turbulent jets to their combined mass flow rate.…”
Section: Numerical Approach and Model Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The burn dependency between pre- and main-combustion chambers was adapted from the already developed and tested concept of a parameter-varying Wiebe function 3,17 with a number of readjustments. Song et al 3,17 reported a high correlation between the mass flow rate of the turbulent jets and the rate of combustion in the main chamber. Thus, they linked the intensity of the turbulent jets to their combined mass flow rate.…”
Section: Numerical Approach and Model Developmentmentioning
confidence: 99%
“…In these equations, m · tur is the mass flow rate of turbulent jets; C p is the specific heat at constant pressure; T tur is the temperature of turbulent jets; E · tur is the rate of energy of turbulent jets; θ Spark is the crank angle degree at the time of spark timing; θ is the instantaneous crank angle degree; E · tur + is the filtered energy term to consider the effect of turbulent jets after spark timing and before top dead center of fire (TDCF) (0 CAD), while the flow direction is from pre- to the main-combustion chamber; β is a calibrating parameter to maintain the burn dependency of the pre- to the main-combustion chamber; b is the mathematical expression for the intensity of turbulent jets; 3,17 θ 0 , Main is the main chamber SOC which is calculated as ...…”
Section: Numerical Approach and Model Developmentmentioning
confidence: 99%
See 3 more Smart Citations